Interaction between microorganisms and dental material surfaces: general concepts and research progress. Issue 1 (31st December 2023) - Tu, Yan; Ren, Huaying; He, Yiwen; Ying, Jiaqi; Chen, Yadong
ABSTRACT: Bacterial adhesion to dental materials' surfaces is the initial cause of dental materials-related infections. Therefore, inhibiting bacterial adhesion is a critical step in preventing and controlling these infections. To this end, it is important to know how the properties of dental materials affect the interactions between microorganisms and material surfaces to produce materials without biological contamination. This manuscript reviews the mechanism of bacterial adhesion to dental materials, the relationships between their surface properties and bacterial adhesion, and the impact of bacterial adhesion on their surface properties. In addition, this paper summarizes how these surface properties impact oral biofilm formation and proposes designing intelligent dental material surfaces that can reduce biological contamination.